Characterization of spatial variation of indoor coverage for HDTV in Singapore (part 1) - Nur Sakinah Ahmad. (2011)
The report begins with an introduction on the Digital Video Broadcasting (DVB) in Singapore; follow-by the background of DVB, the scope of the project and review of theory. Following that, the author will discuss about the equipment used in the project. Next, she will be discussing on the construction of the software; follow-by the user guide instruction on the software provided for the user. The signal that received and analyzed for the project is Channel 42, at 610MHz, MediaCorp HD5, which is a digital TV signal that is currently adapting the DVB-T standard. As the measurement are done and carried indoor, she will also discuss on equipment setup and software usage instruction for the equipment will also be covered under the measurement methodology.